Finite Element Analysis of Solid and Vented Disc - WAN SAKAWI, SYED ABDUL AFIQ; Ismail, Al Emran (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In terms of temperature range, disc brakes have been used for several years and are still improving. To simulate and predict the temperature range of the disc brake, many techniques have been developed. Over time, disc brakes have evolved to be a reliable system for decelerating and stopping a car. For various applications, there have been different prototypes of disc brake systems. A detailed explanation of the different geometries of the components and materials used in the design of disc brakes is given in this research. Despite all the changes, there are still many technical challenges associated with disc brakes that need to be understood and addressed in greater detail. This study deals with the modelling and analysis by SolidWorks and Ansys of solid and ventilated disc brakes. In this research, structural and thermal analysis is performed by using Ansys to fulfil the objective. Comparison can be made for the three-material utilized to suggest the best material for disc brake application.